Value Co-creation by Compulsory Facebook-Community in Corporate Culture: A Case Study Malaysian Logistic Company - Norani Nordin; H.M. Belal; Quamrul Hasan; Michitaka Kosaka (International Journal of Supply Chain Management, 2020)
The main purpose of this study was to investigate the value co-creation process using Facebook as compulsory by a company. A new value co-creation model was developed showing how Facebook could be successfully executed as a platform for the value co-creation process with the aim of providing the best possible service to the recipients. This research employed an explanatory case study due to its uniqueness, especially for sufficient and in-depth comprehension of the phenomenon. PKT Logistics Group Sdn Bhd (PKT) was chosen for this study due to its exceptional characteristic of declaring itself as ‘Facebook compulsory’ company in business after Facebook. Data were obtained from interviews, direct observations, and a questionnaire survey of the company’s top management, selected employees, and customers.The proposed model has successfully connected the company’s leader, employees, and customers with each other for attaining the ‘Ba’ in new knowledge creation spirally using Facebook as an effective platform. This has resulted in the achievement of a service-oriented value co-creation process.This research has contributed to create a new model of the value co-creation process involving all the stakeholders via a ‘Facebook community’, which could be useful for other service providers.This study differentiates itself from the restricted application of Facebook in business by focusing on Facebook as compulsory in a corporate culture. The new value co-creation process model thru a ‘Facebook community’ is original and might be first of this type study.